Productivity versus Endowments : A Study of Singapore's Sectoral Growth, 1974-92 - Kee, Hiau Looi (World Bank, Washington, DC, 2014)
Productivity, and the Rybczynski effects of factor endowments, have been highlighted as the two main reasons behind the growth of newly industrializing economies in East Asia. However, empirical studies at the aggregate level, do not find support for these claims. Focusing on Singapore's manufacturing industries, the author estimates the contributions of productivity, and factor endowments to sectoral growth. The results show that both are important. But productivity is more important as a source of growth in the electronics industry, while factor endowments make a larger contribution in other industries.